Incorrect diagnosis of Clostridium difficile infection in a university hospital in Japan. Issue 10 (October 2015) - Mori, Nobuaki; Yoshizawa, Sadako; Saga, Tomoo; Ishii, Yoshikazu; Murakami, Hinako; Iwata, Morihiro; Collins, Deirdre A.; Riley, Thomas V.; Tateda, Kazuhiro
Abstract Physicians often fail to suspect Clostridium difficile infection (CDI) and many microbiology laboratories use suboptimal diagnostic techniques. To estimate the extent of and reasons for incorrect diagnosis of CDI in Japan, we investigated toxigenic C. difficile isolated from all stool culture samples and clinical course. Over a 12-month period in 2010, all stool culture samples (n = 975) submitted from inpatients in a university hospital in Japan were cultured for C. difficile and routine microbiological testing was conducted. In total, 177 C. difficile isolates were recovered, and 127 isolates were toxigenic. Among the toxin-A-positive/toxin-B-positive isolates, 12 were also positive for the binary toxin gene. However, clinically important ribotypes, such as 027 and 078, were not identified. A total of 58 (45.7%) cases with toxigenic C. difficile had unformed stool, and the incidence CDI was 1.6 cases per 10, 000 patient-days. Of these 58 cases, 40 were not diagnosed in routine testing due to a lack of clinical suspicion (24.1%, 14/58) or a negative C. difficile toxin assay result (44.8%, 26/58). A stool toxin assay was performed in 54 patients (78.2%, 54/69) who did not have unformed stool. The present study demonstrated that a significant number of CDI cases in Japan might be overlooked or misdiagnosed in clinical practice due to a lack of clinical suspicion and limitations of microbiological testing for CDI in Japan. Providing education to promote awareness of CDI among physicians is important to improve the accuracy of diagnosis in Japan.